Tales of Darkness : the Mythology of Evil. - Ellwood, Robert (Bloomsbury Publishing, 2009)
Evil, an undeniable yet inexplicable force in human existence, is often defined as that which ought not to be, yet is - so it must be destroyed, or contained, or lived with. Myths of evil function to universalize the human condition, to show the tension between the ideal and the real, to reveal but not allegorize that condition, and to go some way to assist humanity in understanding, combating and coping with evil within its societies. Tales of Darkness explores the causes of evil in myth, encompassing themes such as defilement, the figure of the trickster, evil people both within and outsi.